THE IMPACT OF ECONOMIC DEVELOPMENT, POLITICS AND SOCIAL CONDITIONS TO FISHERMEN POVERTY IN SURABAYA CITY INDONESIA - Casmiwati, Dewi; Zubir bin Ibrahim, Ahmad; Binti Mohd. Zain, Zawiyah (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to analyze the impact of economics, politics, and social factors on fishermen’s poverty in Surabaya City. The methodology used qualitative case studies in Surabaya City, Indonesia. In the analysis, thematic analysis was used from interviews with 36 informants. Theoretically, this analysis used a structural theory view that saw poverty from an external factor. This consisted of the development process, policy from the government, and social conditions that contributed to fishermen’s poverty. The result showed that all those factors had a negative impact on fishermen’s livelihoods, which meant they supported their poverty. This article will see the impact of these factors contributing to fishermen’s poverty in Surabaya, Indonesia. How they work. Refer to the finding; this research recommends to the Surabaya City government and the central government to protect the environment and marine waters as fishermen’s livelihoods, besides giving subsidies on petrol that is needed for fishing. Also, the government needs to provide staff, capital, and a place to absorb the fishing catches from fishermen and needs to improve the implementation of strict waste disposal regulations to solve the pollution problem.